PLAN OF ORTHOPEDIC AND TRAUMATOLOGY SPECIALIST HOSPITAL - Ritonga, Isniar Tiurma Leonora; Sibarani, Paterson HP; Tioman, Richard (ASTONJADRO, 2021)
Along with the times, the quality and quantity of hospitals in Indonesia also continue to grow. According to Statistics in Indonesia, the number of births in Indonesia is still high, as well as the mortality rate shown by the 2012 medical survey which is also still high. So that improving the quantity and quality of maternal and child is still needed. Based on data from the Ministry of Health of the Republic of Indonesia, pregnant women do not have access to go to midwives or doctors in the regions. Suburban communities, especially in the Medan Sunggal area, do not get adequate services and facilities in terms of health, especially maternal and child health. So with that, the Mother and Child Hospital will be established in the Medan Sunggal area is expected to fullfill the necessities of the community in the suburbs of Medan. The Mother and Child Hospital was designed with the theme of Green Architecture so that the resulting building design is comfortable with an environmentally friendly atmosphere so that it can be considered to be the main destination for everyone who is pregnant and giving birth.